The evaluation of teaching centers: an integrated approach - Pallarés Martínez, Salvador; Catà de la Torra, Ramir Bullich (Avances en Supervisión Educativa, 2007)
The present article analyses the main factors that affects evaluation and resulting change. It also sets a proposal for a new framework for schools’ performance evaluation and sets for an integrated approach in evaluation. In accordance with these theoretical principles, it develops a proposal for evaluation as it is carried out by following the "2005-2009 Evaluation Plan for Catalonia". It provides a description of tools -strategies and technological support- as well as the evaluation process in which all evaluating agents both external and internal are integrated.